Power development in sprint canoeing - Nikonorov, A. (Training sprint canoeing. Progress in improving the physical, technical, tactical, psychological and nutritional preparation, 2015)
Strength development in canoeing is an integrated part of a comprehensive training process, targeted to improve specific canoeing abilities and the effectiveness of training on the water. It is the efficiency of this integration in particular which makes strength development in canoeing different to that in other sports. Concomitantly, the generic sprint canoeing training philosophy is experiencing significant developments since the 200m events were included in the programme of 2012 Olympic Games. The performance over 200 meters is limited by specific factors which cannot be developed efficiently enough via exclusive preparation for the 1000m or 500m events. Also, the racing programme over 200m involves far fewer competitors than the longer distance events. This makes highly unlikely the possibility of preparing athletes for this distance alone, and accentuates the need to optimise the simultaneous progression of abilities to race all distances. The difference in physiological profile between the 200m, and 500m or 1000m events is very important from a coaching perspective. The contribution of athlete's endurance to the eventual performance is still substantial. Stroke rate may drop by more than 10% from its peak by the end of the race. Lactic acid concentration can reach 15-17 mM/L - a similar level to that achieved by 500 and 1000 metre paddlers, but in the time just over 30 seconds. Input from the anaerobic metabolic pathway rises from 40% to nearly 70%. K1 boat speed can reach up to 6.8 m/s and this is usually achieved in the first 50-70m of the race. Stroke rates may exceed 170 strokes per minute, equating to nearly 3 strokes per second. Hence, the duration of the paddle water phase shortens from approximately 0.5s to 0.35s and 0.2s during the marathon, 1000m and 200m races respectively. The application of force on the blade becomes more pronounced with the simultaneous increase in maximum level of force and shortening of the time to apply it. This requires from the athlete produce an "impact effort", than a continuous muscular contraction, and different physical and technical capabilities.